Endeudamiento y morosidad de los clientes MYPES de la caja Trujillo 2007 - 2010 - Vivas Morales, Paul Alfonso (2018)
ABSTRACT The present research work entitled "DEBT AND LIABILITY OF MYPES CLIENTS OF CAJA TRUJILLO 2007 - 2010", has as main objective to determine if the credit procedures of indebtedness significantly influence the delinquency of the MYPES clients of Caja Trujillo 2007-2010 . The research design that was used was of a descriptive type, as well as the deductive-inductive, analytical and synthetic methods, as well as the collection of data from the credit records of the MYPES clients. From the results obtained from the present investigation, a Chi square statistic was applied for each sample in each period, evidencing that all the chi-square values calculated from the respective observations that correspond to the indebtedness in the elements that make up the credit history, the capacity of payment, the income and the financial indebtedness of the MYPES clients according to the delinquency, are greater than the tabulated Chi squares with a level of significance of 5%. Based on the foregoing, it is concluded that there is a statistically significant relationship between indebtedness and delinquency in the MYPES clients of Caja Trujillo.